ANALISIS KREATIVITAS ANAK USIA 5-6 TAHUN DI TK GUDISEJU - Nurhalisa Nurhalisa; Peny Husna Handayani (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to describe the creativity of children aged 5-6 years in Gudiseju Kindergarten, especially from the aspects of fluency, flexibility, originality, elaboration, tenacity and patience during the process of learning activities and free play activities. The research used descriptive qualitative, with observation and interview data collection techniques, on 14 children and 1 teacher at Gudiseju Kindergarten. Data analysis inductively to understand the real picture of children's creativity. The results of the study on the aspect of fluency, there are 10 out of 14 children showing children are able to express their ideas and creativity fluently, showing the ability to imagine and fluent verbal expression. on the aspect of flexibility, there are 14 children showing the ability to adapt and be flexible in creating, able to change and develop their ideas during the activity, both in learning activities and during free play. On the aspect of originality, 12 out of 14 children are able to produce unique and original ideas in their work and behavior that show their own characteristics in creating. In the elaboration aspect, 14 children were able to add details and enrich their work and stories, demonstrating that they did not just stop at the initial idea, but tried to develop it. And in the tenacity and patience aspect, 10 of the 14 children demonstrated success in completing all their activities. The results of this study indicate that a varied learning environment and activities that support freedom of expression and exploration play a significant role in the creativity of children aged 5-6 years at Gudiseju Kindergarten.